Leaf resistance to Botrytis cinerea in wild tomato Solanum habrochaites depends on inoculum composition - You, Yaohua; Astudillo-Estévez, Iván; Essenstam, Bert; Qin, Si; van Kan, Jan A. L. (Frontiers in Plant Science, 2023)
Tomato (Solanum lycopersicum) cv. Moneymaker (MM) is very susceptible to the grey mould Botrytis cinerea, while quantitative resistance in the wild species Solanum habrochaites (accession LYC4) has been reported. In leaf inoculation assays, an effect of nutrient and spore concentration on disease incidence was observed. Resistance in LYC4 leaves was manifested as a high incidence of tiny black, dispersed spots which did not expand ("incompatible interaction") and was pronounced when B. cinerea was inoculated at high spore density (1000 spores/µL) in medium with 10 mM sucrose and 10 mM phosphate buffer. Under the same condition, a high frequency of expanding lesions was observed on MM leaves ("compatible interaction"). Remarkably, inoculation of LYC4 with a high spore density in medium with higher concentrations of sucrose and/or phosphate as well as lower spore density (30 spores/µL) in medium with low sucrose and phosphate, all resulted in a higher percentage of expanding lesions. The lesion sizes at 3 days post inoculation (dpi) differed markedly between all these inoculation conditions. This inoculation method provides a convenient tool to study mechanisms that determine the distinction between compatible and incompatible interactions between B. cinerea and a host plant.